Presentation (Itinera, 2023)
The University of Turin has organized a series of events to celebrate the seventh centenary of Dante's death. The final event included a seminar on Dante and comics, a figurative comment which, despite the different purposes and different audiences, still reminds us that Dante's iconic poetry favors illustrations, in which excellent illuminators have distinguished themselves from the very beginning.